Disobedient Things: The Deepwater Horizon Oil Spill and Accounting for Disaster - David Troy Cochrane (Valuation Studies, 2020)
Analysis of the Deepwater Horizon disaster and the accumulative decline of BP demonstrate both the analytical efficacy of the capital-as-power approach to value theory, and the irreducible role of objects in the process of accumulation. Rather than productivity per se, accumulation depends on (1) control of productivity, and (2) the evaluation of control. Capital-as-power focuses on capitalization as an expression of the evaluation by owners of their own power. In this article, I argue that the power of owners translated into capital values is power over both the human and non-human components of systems of production. Power is actualized through entities defined as cultural and political, as well as economic. Capitalization translates into the commensurable financial units of capital the irreducible social order—including objects—that bears on accumulation. The decline of BP's capital valuation in the wake of the disaster expressed the market's falling confidence in the expertise, experience and equipment that comprised the company's productive capacity.
Keywords: P16; G; G01; P28; Q4; 330; capital accumulation; crisis; things; value